Characterization of the promoter region of the src family gene lyn and its trans activation by human T-cell leukemia virus type I-encoded p40tax. - Uchiumi, F (1992)
The src family gene lyn is expressed preferentially in B lymphocytes but very little in normal T lymphocytes. Transcription of the lyn gene in T lymphocytes was shown to be induced by the p40tax protein encoded by human T-cell lymphotropic virus type I. For determination of the mechanism of p40tax-mediated trans activation, the transcriptional promoter region of the lyn gene was characterized. By endonuclease S1 mapping, the transcriptional initiation sites were identified within the 770-bp EcoRI-SacI fragment of the 5'-terminal portion of the human lyn gene. This fragment showed promoter activity when placed upstream of the bacterial chloramphenicol acetyltransferase gene and transfected into various cell lines. Nucleotide sequence analysis revealed that the lyn promoter region contained four GC box-like sequences but not a TATA or CCAAT box. In addition, it contained sequences characteristic of a cyclic AMP-responsive element, octamer-binding motif, PEA3-like motifs, and NF kappa B-binding motif-like sequence. Mutational analysis suggested that the octamer-binding motif sequence is of primary importance for the lyn promoter activity but that the other elements are not. Cotransfection of various chloramphenicol acetyltransferase constructs containing different length of the lyn promoter together with p40tax expression plasmids into Jurkat T cells showed that the sequence responsible for p40tax-induced transcription is present around the transcription initiation sites.